Mimicking an Atomically Thin "Vacuum Spacer" to Measure the Hamaker Constant between Graphene Oxide and Silica. Issue 5 (22nd December 2016) - Chu, Liangyong; Korobko, Alexander V.; Cao, Anping; Sachdeva, Sumit; Liu, Zhen; de Smet, Louis C. P. M.; Sudhölter, Ernst J. R.; Picken, Stephen J.; Besseling, Nicolaas A. M.
Abstract : The Hamaker constant between graphene oxide and silica, which quantifies the strength of van der Waals forces is determined, by mimicking a "vacuum spacer" in an atomic force microscopyforce tudy. It is demonstrated that, a 2D spacer is expected to yield an accurately defined separation, owing to the high atom density and strength in planar direction compared with other dimensional spacers.